Strategi Kebijakan Impor Sapi Berbasis Manajemen Risiko di Masa Pandemi - Firmansyah Firmansyah; Yandra Arkeman; Irma Isnafia Arief (Jurnal Ilmu Pertanian Indonesia, 2023)
This study aims to analyze potential risks and risk mitigation in the company's supply chain to minimize the company's potential losses and develop a policy strategy for importing feeder cattle during the COVID-19 pandemic as a framework (blueprint) for company readiness in the future as well as in handling food security, especially to meet the domestic demand for beef, which is currently only able to meet 70% of the total demand. In the early stages of the research, the House of Risk (HOR) method is employed to identify risk variables (risk events and risk agents) and risk mitigation. The results obtained from the risk analysis are used to develop corporate policy strategies. The results of the ANP-BOCR analysis show that the policy strategy that is set as the highest priority is the improvement and enhancement of operation and production processes (PPOP). The alternative policy strategy with the lowest priority is implementing a Go-Public (KGP) policy. Improvement and enhancement of operation and production processes carried out in the company include: 1) application of complete feed; 2) production efficiency and mechanization; and 3) implementation of Internet of Things (IoT) and Digitalization. The results of the Rater Agreement (W) show that all respondents (experts) have a fairly high agreement on the priority of the policy strategy set, with Kendall's W coefficient value of 0.5. Keywords: analytic network process, BOCR, Covid-19, house of risk